A comparative analysis of the comprehension of children with mild mental retardation using cartoonized illustration and puppetry - Macasaet, Roma Sauz (Animo Repository, 2007)
This study aimed to determine the usefulness of two types of visual presentation media in enhancing story comprehension among children with mild mental retardation. Ten students with mild mental retardation from the Independent Living Learning Center (ILLC) in Wack-Wack, Mandaluyong participated in this study. They were divided equally into two groups: Group A, the cartoonized illustration group, and Group B, the puppetry group. Two types of visual presentation media were used as treatment materials for the three stories: (1) The Little Pink Rose (2) The Little Red Hen and (3) The Giving Tree. Treatment 1 referred to the cartoonized illustration and treatment 2 referred to the puppetry. However, group A was exposed to treatment 1 while group B was exposed to treatment 2. Both groups were presented with the same stories. A comprehension test was given immediately after the story presentation. Based on the results, children with mild mental retardation understood stories better when cartoonized illustrations were used. It is therefore concluded that fixed and distinct instructional materials are essential in facilitating comprehension in story reading among children with mild mental retardation.